Comparação entre índices dinâmicos e volumétricos de pré-carga em cães submetidos à hemorragia moderada seguida de reposição volêmica - Celeita-Rodríguez, Nathalia [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Objective: To evaluate the effects moderate blood loss followed by volume replacement (VR) on intra-thoracic blood volume index (ITBVI), global end-diastolic volume index (GEDVI), pulse pressure variation (PPV), and stroke volume variation (SVV). Study design: Prospective, randomized study. Animals: Seven English Pointer dogs (20.0–31.2 kg). Methods: Anesthesia was maintained with sevoflurane under volume-controlled ventilation and atracurium induced neuromuscular blockade. End-expired sevoflurane (ETsevo) concentrations were adjusted to inhibit heart rate and mean arterial blood pressure (MAP) changes in response to nociceptive stimulation (< 20% relative change). Data recorded at baseline, after withdrawal of 14–16 mL kg-1 of blood volume and after VR with autologous blood. Results: Anesthesia was maintained with 3.1 ± 0.3 vol% of ETsevo concentrations. One outlier was excluded from the statistical analysis. Hemorrhage significantly (P < 0.05) decreased cardiac index (CI), stroke index (SI), and MAP by 20–25% from baseline (percent changes in mean values). Volume replacement significantly increased MAP in comparison to values recorded after hemorrhage (31% increase); while CI and SI were significantly increased after VR in comparison hemorrhage and to baseline (29–30% above baseline). The ITBVI and GEDVI were decreased by 15% from baseline after blood loss; while VR significantly increased ITBVI and GEDVI by 21% from values recorded after hemorrhage. Relative decreases in ITBVI induced by hemorrhage represented 10–44% of the blood volume withdrawn among individual animals. No significant changes in PPV and SVV were observed throughout the observational period. Conclusions and clinical relevance: Volumetric indexes of preload, but not PPV and SVV, reflect changes in volume status induced by moderate blood loss and VR. However, a high inter-individual variability of changes in ITBVI and GEDVI induced by similar degrees o hemorrhage suggest that these indexes are inaccurate estimate the severity of acute hemorrhage.

Objetivo: Avaliar os efeitos da perda moderada de sangue seguida por reposição volêmica (RV) no índice de volume sanguíneo intratorácico (ITBVI), índice do volume global diastólico final (GEDVI), variação da pressão de pulso (VPP) e variação do volume sistólico (VVS). Delineamento experimental: Estudo prospectivo aleatorizado. Animais: Sete cães da raça Pointer Inglês (20 a 31,2 kg). Métodos: A anestesia foi mantida com sevofluorano sob ventilação mecânica no modo volume controlado com bloqueio neuromuscular induzido pelo atracúrio. A concentração expirada de sevofluorano (ETsevo), foi ajustada de forma a inibir alterações na frequência cardíaca e na pressão arterial média (PAM) em resposta à estimulação nociceptiva (< 20% mudança relativa). As variáveis estudadas foram registradas no momento basal, após retirada de 14 a 16 mL/kg da volemia e após a RV com sangue autólogo. Resultados: A anestesia foi mantida com 3,1 ± 0,3% de ETsevo. Um animal discrepante (“outlier”) não foi incluído da análise estatística. A hemorragia diminuiu significativamente (P < 0,05) o índice cardíaco (IC), índice sistólico (IS) e PAM em 20-25% dos valores basais (variações percentuais nos valores médios). A RV aumentou significativamente a PAM em relação aos valores registrados após hemorragia (31% de aumento); enquanto o IC e IS elevaram-se significativamente após a RV (29-30% acima dos valores basais). Após a hemorragia, o ITBVI e GEDVI se reduziram significativamente em 15% em relação aos valores basais; após a RV estas variáveis aumentaram significativamente em 21% em relação ao final da hemorragia. A diminuição relativa no ITBVI induzida pela hemorragia representou 10-44% do volume sanguíneo removido dos animais. Não houveram alterações significativas na VPP e VSS durante o estudo. Conclusões e relevância clínica: Os índices volumétricos de pré-carga, mas não VPP e VVS, refletem mudanças no volume circulante induzidas pela hemorragia moderada seguida por RV. Porém, a elevada variabilidade interindividual nas mudanças do ITBVI e GEDVI induzidas por graus semelhantes de perda volêmica sugere que estes índices são imprecisos para se estimar a severidade da hemorragia aguda.
Comparison between dynamic and volumetric preload indexes in dogs undergoing moderate hemorrhage followed by volume replacement with autologous blood
Keywords: Transpulmonary thermodilution; Pulse pressure variation; Stroke volume variation; Global end-diastolic volume; Intrathoracic blood volume; Termodiluição transpulmonar; Variação da pressão de pulso; Variação do volume sistólico; Volume sanguíneo intratorácico; Volume diastólico final global